Representasi Bentuk-Bentuk Puisi Modern dalam Kumpulan Puisi Empat Kumpulan Sajak Karya W.S Rendra - Haris, Abdul; Juliawan, Rizcky (BAHTRA: Pendidikan Bahasa dan Sastra, 2024)
The aim of this research is to describe and examine the forms of modern poetry in the poetry collection Four Collections of Poems by W. S Rendra. This research is of qualitative type. The method used in this research uses descriptive analysis and literature study methods. Research data sources are primary and secondary. Primary data comes from the book EKS poetry collection by W.S Rendra which was published by the publisher Burungmerak Press in 2010. Secondary data comes from books and research journals that are relevant to this research. This research data is in the form of phrases and sentences. The data collection technique in this research uses documentation techniques, including critical and comprehensive reading activities, recording and processing data. The data analysis technique for this research uses qualitative descriptive analysis techniques. The results of the research are that in the EKS poetry collection by W.S Rendra there are various forms of modern poetry based on the number of lines, including distikon, terzina, quatrines, kuin, sextet, septima, stanza. Of the seven forms of modern poetry based on the number of lines, only the sonnet form is not found in the EKS poetry collection by W.S Rendra.